The Role of Oposition Parties: A Systematic Literature Review (SLR) - Devina Anggraeni; Phone Pyae Soe (Konsultan Surya Buanan, 2024)
Opposition parties in Indonesia today, especially during President Jokowi's first government period (2014-2019) and second period (2019-2024), many have failed to carry out their function as political watchdogs and cooperate well with the government, which has resulted in instability in the landscape. state politics. This research aims to understand the impact of party opposition on the stability of Indonesian democracy. The research methodology used in this research is a systematic literature review using 192 scientific articles sourced from the Scopus database. Articles reviewed using the Vosviewer application. Based on the findings of this research, opposition parties have a significant impact on the development of democracy in the Indonesian political system because they provide good stability for the reform of the country's political system. Opposition parties in parliament have different methods from the agreed government. Opposition parties can work together in various ways, for example by criticizing government policies.